Infant Warmer with Digital Scales for Auto Adjustment PID Control Parameters - Anita Miftahul Maghfiroh; Farid Amrinsani; Singgih Yudha Setiawan; Rafi Maulana Firmansyah; Shubhrojit Misra (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
Babies need temperatures that match the temperature of the mother's womb, which is between 35°C – 37°C. The latest research on infant warmer device used fuzzy method as a system for controlling temperature in infant warmers. The problem raised in the previous research is that the temperature was not evenly distributed throughout the bed at each predetermined temperature setting. When it reached the setting temperature, the warmer continued to turn on so that the bed got hotter. Therefore, the purpose of the current research is to make an infant warmer device equipped with digital scales with a temperature setting of 350C- 370C using PID control to stabilize the temperature and ensure that the heat is evenly distributed on the bed. In addition, skin temperature is also added, allowing the nurses know at which level of patient's body temperature is when observations should be made. The infant warmer in this module used an arduino microcontroller which is displayed in 7 segments, the skin sensor used is the DS18B20 temperature sensor to read the skin temperature, while the infant warmer temperature sensor used is LM35 as a PID control system. The results of the current research in making the device module were compared with the measurement results of the comparator. It was revealed that current research has obtained smallest error of 0% in temperature setting of 350C. For the comparison with the incu analyzer, the smallest error was obtained at the temperature setting of 370C with an error value of 0% on the T5 measurement. Meanwhile, the difference in skin temperature against the thermometer is 0.10C. The results showed that the temperature distributed on the module had different error values. Hence, this research can be implemented on the PID control of infant warmer system to improve the performance of infant temperature stability.